Pendugaan bobot badan melalui analisis morfometrik dan status reproduksi kambing Jawarandu betina di Kecamatan Samarinda Utara - Dewi Anggraeni; Surya Rahmatullah (Universitas Mulawarman, 2021)
ABSTRACTThis study aims to determine the regression equation between body size and body weight of ewe Jawarandu goats in North Samarinda District, to know the characteristics of the reproductive status of ewe Jawarandu goats in North Samarinda District and to know morphometric analysis based on body size of ewe Jawarandu goats in North Samarinda District. Data collection was carried out by interviewing breeders and direct observation in the field of sampling was carried out using purposive sampling method, namely purposive sampling technique based on certain considerations.The results showed that the age at first mating was 11.00 ± 1.43 months the average age first partus was 16.00 ± 1.42 months, the average estrous cycle was 19.33 ± 1.33 days, litter size on average 1.42 ± 0.50. Mean values and standard deviation of girth 74.53 ± 2.93, body legth 64.78 ± 4.06, shoulder height 70.22 ± 3.07 and body weight 36.10 ± 4.27. The chest circumference, body length and shoulder height of ewe Jawarandu goats had a significant effect on body weight and the type of birth of ewe Jawarandu goats was higher than the type of birth of twins. Keywords: Estimation, morphometrics and reproduction.